2015
DOI: 10.1371/journal.pone.0139952
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in CAM and Non-CAM Users among Breast Cancer Patients during Chemotherapy in Malaysia

Abstract: BackgroundComplementary and alternative medicine (CAM) use has become increasingly popular among patients with cancer. The purposes of this study were to compare the QOL in CAM users and non-CAM users and to determine whether CAM use influences QOL among breast cancer patients during chemotherapy.MethodologyA cross-sectional survey was conducted at two outpatient chemotherapy centers. A total of 546 patients completed the questionnaires on CAM use. QOL was evaluated based on the European Organization for Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 32 publications
7
34
2
5
Order By: Relevance
“…Similar findings were also reported in studies done elsewhere [10,11]. Ethiopia is among one of the poorest countries in the world.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar findings were also reported in studies done elsewhere [10,11]. Ethiopia is among one of the poorest countries in the world.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study showed that there were no considerable differences between CAM consumers and non-CAM consumers in QoL. This finding corroborate a study conducted by Chui et al [10][11][12] that reported no considerable differences in QoL between CAM consumers and non-CAM consumers in Malaysia and Turkey, respectively. Similarly, a study done in Korea by Kang et al [34] and in Germany by Tautz et al [33] found out that the global QoL of breast cancer patients between CAM consumers and nonconsumers was not different.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Verilerin toplanmasında araştırmacılar tarafından literatür incelemesi sonrasında geliştirilen; (4,5,13,(15)(16)(17)(18) (1) Katılımcıların Sosyodemografik ve Hastalığa İlişkin Özelliklerine Ait Form, (2) Tamamlayıcı Sağlık Yaklaşımları Kullanımına İlişkin Form ve (3) İlaçlar Hakkında İnançlar Anketi kullanılmıştır.…”
Section: Veri Toplama Araçlarıunclassified
“…Hastaların tamamlayıcı sağlık yaklaşımları kullanma durumları ile hangi tamamlayıcı sağlık yaklaşımları yöntemini kullandığı, kullanma nedeni ve kimin önerdiği sorgulanmıştır. (5,4,13,15,16,18) İlaçlar Hakkında İnançlar Anketi: Horne ve ark. (19) tarafından geliştirilen "İlaçlar Hakkında İnançlar Anketi" ile bireylerin kendilerine reçete edilen ilaçlar ve genel olarak ilaçlar hakkındaki kişisel görüşlerini ölçmek amaçlanmaktadır.…”
Section: Tamamlayıcı Sağlık Yaklaşımları Kullanımına İlişkin Formunclassified